Towards an Agile-Based Integrated Management Systems Framework - Francisco, Fernanda E. [UNESP]; Kimura, Issao [UNESP]; de Nadae, Jeniffer; Carvalho, Cleginaldo P. [UNESP]; Carvalho, Marly M. [UNESP]; Santos, Gilberto; Oliveira, Otávio J. [UNESP] (Technical University of Kosice, 2024)
Purpose: We propose an unprecedented model for incorporating agile methodology (AM) into the development of an Integrated Management System (IMS). Design/Methodology: The research design employed a literature review and content analysis approach. We identified ten distinct IMS models from academic literature and subjected them to critical cross-analysis. Additionally, we conducted an exhaustive review of seminal agile literature to pinpoint essential characteristics of both AM and IMS. Findings: The comprehensive content analysis and coding process facilitated identifying fundamental agile elements to be integrated into the proposed framework. As a result, we present an interdisciplinary Agile-based Integrated Management System (AIMS) framework. Originality: This framework draws upon insights from diverse research sources and introduces a three-level analysis perspective: strategic, tactical, and operational. Integrating IMS with AM empowers organisations to make more agile and responsive decisions concerning IMS implementation. Within this framework, the IMS backlog is defined concurrently with its development, reflecting an adaptive approach in contrast to the conventional project scope delineation.
Keywords: agile methodologies; certifiable management systems; integrated management system